Penerapan Realistic Mathematics Education untuk Meningkatkan Aktivitas dan Hasil Belajar Siswa - Salma Salma; Dewi Pramita; Vera Mandailina; Syaharuddin Syaharuddin (Justek : Jurnal Sains dan Teknologi, 2020)
Abstract: The purpose of this study is to find out the improvement of student activities and learning outcomes with the implementation of Realistic Mathematics Education (RME).  This research uses Class Action Research. As the subject in this study were grade VII MTs students as many as 23 people. Data analysis techniques used are qualitative and quantitative to measure the increase in student activity and learning outcomes. Based on the results of the research, it can be concluded that the application of RME can improve student activities and learning outcomes. This can be seen from the increase in learning activities in the first cycle obtained an average percentage of 55% with a fairly good category, increased by an average percentage of 85% fall into the category of excellent in cycle II. While student learning activities have increased from cycle I with an average percentage of 55% fall into the category quite well to 85% with a very good category in the second cycle. Classical student completeness also increased in cycle I was 56.52% and in cycle II by 86.95%. Abstrak: Tujuan dari penelitian ini untuk mengetahui peningkatan aktivitas dan hasil belajar siswa dengan penerapan Realistic Mathematics Education (RME).  Penelitian ini menggunakan Penelitian Tindakan Kelas (PTK). Sebagai subjek dalam penelitian ini adalah siswa kelas VII MTs sebanyak 23 orang. Teknik analisis data yang digunakan adalah kualitatif dan kuantitatif untuk mengukur peningkatan aktivitas dan hasil belajar siswa. Berdasarkan hasil penelitian dapat disimpulkan bahwa penerapan RME dapat meningkatkan aktivitas dan hasil belajar siswa. Hal ini terlihat dari adanya peningkatan aktivitas pembelajaran pada siklus I diperoleh rata-rata persentase sebesar 55% dengan kategori cukup baik, mengalami peningkatan dengan rata-rata persentase sebesar 85% termasuk dalam kategori sangat baik pada siklus II. Sedangkan aktivitas belajar siswa mengalami peningkatan dari siklus I dengan rata-rata persentase sebesar 55% masuk dalam kategori cukup baik menjadi 85% dengan kategori sangat baik pada siklus II. Ketuntasan klasikal siswa juga mengalami peningkatan pada siklus I adalah 56,52% dan pada siklus II sebesar 86.95%.